1997
DOI: 10.1046/j.1471-4159.1997.68062435.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Transporter Gene Expression in the Central Nervous System in Diabetes Mellitus

Abstract: Diabetic animals exhibit altered neurotransmission in brain monoaminergic systems. By means of in situ hybridization, we have investigated the expression of dopamine, noradrenaline, and serotonin transporter (DA-T, NA-T, and 5-HT-T, respectively) mRNAs in the brains of alloxan-and streptozotocin-diabetic rats. The expression of DA-T mANA is decreased in 1-(-11%) and 4-(-17%) week alloxan-diabetic and 4-(-9%) and 8-20%) week streptozotocin-diabetic rats in the ventral medial bundle. The expression of NA-T mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The comparatively greater effect of diabetes on serotonin-induced vasoconstriction is interesting in view of evidence linking enhanced serotonergic activity, both at serotonin receptors and the serotonin transporter, to pulmonary hypertension [ 26 , 27 ]. Serum serotonin concentrations are elevated in diabetics [ 28 ] and there is evidence for up regulation of the serotonin transporter in platelets [ 29 ] and brain [ 30 ]. These effects may well contribute to the increased prevalence of pulmonary hypertension in diabetics, because over expression of the serotonin transporter in mice causes pulmonary hypertension [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively greater effect of diabetes on serotonin-induced vasoconstriction is interesting in view of evidence linking enhanced serotonergic activity, both at serotonin receptors and the serotonin transporter, to pulmonary hypertension [ 26 , 27 ]. Serum serotonin concentrations are elevated in diabetics [ 28 ] and there is evidence for up regulation of the serotonin transporter in platelets [ 29 ] and brain [ 30 ]. These effects may well contribute to the increased prevalence of pulmonary hypertension in diabetics, because over expression of the serotonin transporter in mice causes pulmonary hypertension [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…WAN are sensitive to various metabolic perturbances, responding either by changes in activity or in measures of injury. Metabolic challenges, e.g., glucose or oxygen dyshomeostasis, influence WAN activity (Figlewicz et al, 1996, Petrisic et al, 1997). Prominent age-related changes in WAN include loss of dendrites, axonopathy, reduction in neurotransmitter synthesis enzymes and, in select populations, lipofuscin accumulation and cell loss (Mann, 1983, Ishida et al, 2001, Zecca et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, i.c.v. STZ caused impairment of passive avoidance behaviour, and both working and reference memory (Mayer et al 1990;Blokland and Jolles 1993;Lannert and Hoyer 1998;Prickaerts et al 1999), most probably as a result of cholinergic deafferentiation (Hellweg et al 1992) and changes in monoaminergic neurotransmission (Lackovic and Salkovic 1990;Ding et al 1992;Salkovic et al 1995;Petrisic et al 1997;Sharma and Gupta 2001;Salkovic-Petrisic and Lackovic 2003). Various experimental and methodological approaches used by different investigators have clearly shown that i.c.v.…”
mentioning
confidence: 99%